Helden auf Hengsten. Das Kriegspferd als Statussymbol im Mittelalter - Clauss, Martin (Viator (English and Multilingual Edition), 2011)
Abstract Medieval knights and men-at-arms rode stallions into battle. This practice is best explained by the function of the warhorses as status symbols. As such warhorses could communicate their riders’ or owners’ status to society mainly for three reasons. They were expensive and thus exclusive. Warhorses were trained and bred especially for warfare and made their riders’ connection with warfare visible. Moreover stallion warhorses required considerable skill and training. Only those whose position guaranteed them time and wealth for extensive training were able to handle warhorses. For these reasons warhorses were understood as symbols of status, first and foremost for the elevation of status (Statuserhöhung) but also for its reduction (Statusminderung). It is this connection between value and type of horse and the status of its rider that made stallions more desirable for medieval knights than mares or geldings.